Design of a high sensitivity and low power ultrasound receiver with a high-resolution SAR ADC for photoacoustic sensing and imaging - Yang, Chuanshi (Nanyang Technological University, 2020)
Photoacoustic (PA) imaging and sensing based on optical excitation and acoustic detection are emerging recently. The main issue of the PA systems is the poor SNR at the output of the sensors. The power consumption and size of the receiver are also crucial for the systems. Thus, several techniques are proposed in the analog front-end (AFE) and the analog-to-digital convertor (ADC) to improve the output SNR and power efficiency of the receiver. A resonant noise matching (RNM) technique is proposed to improve the sensitivity of ultrasound transducers. Diverse from the power matching which aims to maximize the output power from transducer in conventional electrical impedance matching (EIM) technique, the RNM maximizes the output voltage. The advantage of RNM is that it can also equivalently reduce the LNA’s input-referred noise and thus minimize the noise figure (NF) of the ultrasound receiver. Measurement results show that, the output signal is improved by 5 times through the proposed RNM technique, which is 66.7% larger than that of conventional methods. In addition, the sensitivity of the receiver is significantly improved by more than 10.4 dB which is beneficial for a variety of applications of piezoelectric ultrasound transducers. Thereafter, a high sensitivity and high dynamic range AFE is developed and fabricated in TSMC 65 nm CMOS process. An LNA with 30 dB gain and low input-referred noise (1 nV/Hz) is designed to amplify the input signal and suppress the noise from subsequent stages. Then a 3rd order Butterworth low-pass filter (LPF) with 5-20 MHz cut-off frequency is connected behind the LNA to reduce the out-of-band noise. Finally, a variable gain amplifier (VGA) which covers a gain range 0-45 dB with 20 MHz bandwidth are implemented in the AFE. The AFE is also applied in a photoacoustic sensor system which can achieve coherent lock-in function to detect weak PA signals noninvasively at in-vivo environments. An asynchronous SAR ADC with a novel mismatch error shaping (MES) technique is designed and fabricated. The power dissipation of the SAR ADC is dominated by the comparator, DAC and digital logic circuits. To reduce digital power consumption, the asynchronous timing sequence is adopted. As known, the resolution of SAR ADC is limited by the non-linearity of DAC and noise of comparator. The linearity of the DAC can be efficiently improved by the MES technique. The proposed novel MES technique can remove the flash ADC and DWA digital circuits in the convention MES technique, and thus improve the power efficiency. Noise shaping technique is also applied in the SAR ADC to reduce the comparator noise and improve the output SNR. In addition, another MES technique based on a double input range SAR ADC is also proposed. Through this method, the input signal is not necessary to be reduced by 2 times, which happens in the first proposed MES. Consequently, the output SNR can be improved by 3 dB. Overall, the main contributions of the thesis are: a) the RNM technique which is designed to improve the sensor’s sensitivity, b) A 0.18µVrms super-sensitivity photoacoustic imager based on coherent detection for deep in-vivo imaging and c) a low power and high-resolution SAR ADC with improved MES technique.